ANALISIS PENGARUH VARIASI WEIGHT ROLLER DAN SPRING CVT TERHADAP TORSI MESIN K20 125 CC TAHUN 2020 - Reinaldi Teguh Setyawan (Politeknik Negeri Bengkalis, 2022)
The government's lack of attention to comfortable and safe public transportation and the lack of public interest in using public transportation make motorized vehicles chosen for transportation problems. Motorcycles are the most popular form of transportation for the general public. There are two types of transmission in motorcycles, namely manual transmission and automatic transmission. In this test, we compare the 12 gr weight roller owned by the K20 engine with variations of 10,11 and 13 gr on the resulting fuel consumption. The method used in this research is experimental. The tool used is Dynotest. The material used is a motorcycle with a 2020 125 cc K20 engine code which is installed with heavy rollers measuring 10, 11, 12, and 13 grams, after testing, the torque results obtained using a weight roller size 11 produces a better peak torque of 11, 41 gr at 4000 rpm. Using a 10 gram weight roller at 2000 RPM is very small the torque goes up to 3000 RPM getting better results at 11.09 Nm, the peak is at 4000 RPM which is 11.52 Nm and down at 5000 RPM which is 10.81 Nm. The size of the 11 gr weight roller at 2000 RPM is very small, the torque goes up to 3000 RPM to get better results, namely 10.02 Nm, the peak is at 4000 RPM, which is 11.41 Nm and down at 5000 RPM, which is 11.15 Nm. Keywords : Transmission,Roller, CVT, Spring CVT, dynotest, SFC.